Answer:
Jane: 37 years old
Anne: 17
Step-by-step explanation:
Jane 12 years ago: 5x
Anne 12 years ago: x
In three years into the future:
Jane: 5x+15
Anne: x+15
CURRENT TIME:
Jane: 5x+12
Anne: x+12
Equation (using 3 years into the future ages): 5x+15=2(x+15)
5x+15=2x+30
(subtract 15 from both sides)
5x=2x+15
3x=15
x=5
Therefore, Jane is 37 years old and Anne is 17 years old.
Answer: x = 6
Step-by-step explanation:
X - (-4) = 10
X + 4 = 10
X = 10 - 4 = 6
Answer:
g(f(x)) = -6x+6.
Step-by-step explanation:
It is given that,
f(x) = -3x + 2 and g(x) = 2x – 5
We need to find g(f(x)).
Put it into g(x).
g(f(x)) = 2(-3x + 2)+2
= -6x+4+2
=-6x+6
Hence, the value of g(f(x)) is -6x+6.